Formation and Dissociation of the BSS1 Protein Complex Regulates Plant Development via Brassinosteroid Signaling. Issue 2 (6th February 2015) - Shimada, Setsuko; Komatsu, Tomoyuki; Yamagami, Ayumi; Nakazawa, Miki; Matsui, Minami; Kawaide, Hiroshi; Natsume, Masahiro; Osada, Hiroyuki; Asami, Tadao; Nakano, Takeshi
Abstract : BSS1 forms a complex with a master regulator of brassinosteroid signaling, thereby restricting the regulator to the cytosol and negatively regulating brassinosteroid signaling. Abstract: Brassinosteroids (BRs ) play important roles in plant development and the response to environmental cues. BIL1/BZR1 is a master transcription factor in BR signaling, but the mechanisms that lead to the finely tuned targeting of BIL1/BZR1 by BRs are unknown. Here, we identified BRZ-SENSITIVE-SHORT HYPOCOTYL1 (BSS1) as a negative regulator of BR signaling in a chemical-biological analysis involving brassinazole (Brz ), a specific BR biosynthesis inhibitor. The bss1-1D mutant, which overexpresses BSS1, exhibited a Brz -hypersensitive phenotype in hypocotyl elongation. BSS1 encodes a BTB-POZ domain protein with ankyrin repeats, known as BLADE ON PETIOLE1 (BOP1), which is an important regulator of leaf morphogenesis. The bss1-1D mutant exhibited an increased accumulation of phosphorylated BIL1/BZR1 and a negative regulation of BR -responsive genes. The number of fluorescent BSS1/BOP1-GFP puncta increased in response to Brz treatment, and the puncta were diffused by BR treatment in the root and hypocotyl. We show that BSS1/BOP1 directly interacts with BIL1/BZR1 or BES1. The large protein complex formed between BSS1/BOP1 and BIL1/BZR1 was only detected in the cytosol. The nuclear BIL1/BZR1 increased in the BSS1/BOP1 -deficient background and decreased in the BSS1/BOP1 -overexpressing background. Our study suggests that the BSS1/BOP1 protein complex inhibits the transport of BIL1/BZR1 to the nucleus from the cytosol and negatively regulates BR signaling.